Road Safety Reimagined: Exploring Causes, Effects, and Innovative Educational Interventions for Accident Prevention - Fowode, Kayode V.; Nwaogazie, Ify L. (An Overview of Literature, Language and Education Research Vol. 7, 2024)
This chapter is focused on road traffic accidents, exploring the causes and effects of road traffic accidents as well as the safety education intervention that could be employed to enhance the knowledge and awareness of motorists so as to prevent road traffic accidents. In the course of the study regional disparities in road safety were explored. Based on the content explored in this chapter, revealed that road accidents are a major cause of morbidity and mortality worldwide, especially in low and middle-income countries due to poor road infrastructures and poor knowledge and attitude towards driving. It was also noted that road accidents are caused by a number of factors which include environmental factors, vehicle factors (road pavement condition factors, and vehicle operator or driver factors). It was also finally stated that Safety Education Intervention which comprises safety training intervention, supportive supervision and capacity building are key intervention programs that can be adopted to enhance the knowledge and awareness of road users in order to reduce the prevalence of road accidents.